Discontinuous to continuous transition changeover and magnetic helicity reversal in helimagnet nanodisks under torsion - Xuejin Wan; Anruo Zhong; Yangfan Hu; Xiaoming Lan; Biao Wang (New Journal of Physics, 2024)
A magnetic skyrmion is topologically protected because it possesses a non-zero topological charge. As a result, the creation or annihilation of a magnetic skyrmion is thought to be initiated by a sudden reversal of local magnetization, and thus cannot occur continuously. Here, we show that this viewpoint is only partially correct by studying the creation and annihilation of an isolated skyrmion in a nanodisk suffering coupled magnetic field and mechanical torsion. It was found that at a proper magnetic field, the torsion-induced chiral stress field can change the helicity of the magnetization structure and create or annihilate isolated skyrmion in a continuous way. In the torsion-magnetic-field phase diagram, there appears a critical point, where the type of the topological transition changes from a discontinuous to a continuous one. It was further proved that the critical condition for the continuous transition is the softness of magnetization at the center.